Impact of diseases and pests on premature fruit drop in sweet orange orchards in São Paulo state citrus belt, Brazil - Moreira, Rafaele Regina; Machado, Franklin Jackson; Lanza, Fabrício Eustáquio; Trombin, Vinícius Gustavo; Bassanezi, Renato Beozzo; de Miranda, Marcelo Pedreira; Barbosa, José Carlos [UNESP]; da Silva Junior, Geraldo José; Behlau, Franklin (Wiley, 2022)
Background: Despite technical improvements in the citrus chain and leadership in orange production achieved in the past decades, premature fruit drop remains a major component of crop loss in São Paulo state citrus belt, the largest sweet orange production area in the world. The present study aimed to determine, during five consecutive seasons, the impact of the diseases and pests on premature fruit drop in the orange belt. Results: Fruit drop due to the main diseases and pests averaged approximately 11.0%, which corresponded to approximately 63% of the annual fruit drop. The average fruit drop rate due to fruit borer and fruit flies combined was 4.0%, Huanglongbing (HLB) 3.3%, black spot 2.6%, leprosis 1.0% and citrus canker 0.3%. The average amount of fruit drop (million 40.8 kg boxes) and value of crop losses (million US$ dollars), in five seasons, were 12.7 and 66.2 for fruit borer/fruit flies, 11.0 and 57.9 for HLB, 8.1 and 42.2 for black spot, 3.1 and 15.6 for leprosis, and 0.9 and 4.9 for citrus canker, respectively. Conclusion: Fruit borer and fruit flies (combined), HLB, black spot, leprosis and citrus canker are, in this order, the main diseases and pests in the orange belt of São Paulo state. All of these causes significantly increased the overall fruit drop rate in the evaluated seasons. The results will contribute to the development of the Brazilian citrus industry, while showing to other citrus-growing regions the potential that diseases and pests have to jeopardize production. © 2022 Society of Chemical Industry.
Keywords: Anastrepha spp.; Candidatus Liberibacter asiaticus; Ceratitis capitata; citrus leprosis vírus-C; Gymnandrosoma aurantianum; Phyllosticta citricarpa; Xanthomonas citri subsp. citri